Firm Investment, Corporate Finance, and Taxation - Palomba, Geremia (IMF Working Papers; Working Paper ;, 2002)
This paper examines the intertemporal effect of corporate income taxation on the investment behavior of a firm that faces imperfect capital markets. It shows that when capital markets are imperfect, the optimizing firm goes through different phases of growth. In this dynamic setting, the effect of a corporate tax on profits varies over time. An increase in the corporate profit tax rate initially reduces investment, but the effect is reversed over time as the firm adjusts its financing policy to the new tax rate.